The central bank "printing press": Boon or bane? Remedies for high unemployment nd fears of fiscal crisis - Greg Hannsgen; Dimitri B. Papadimitriou (Levy Economics Institute of Bard College, 2010)
In recent years, the US public debt has grown rapidly, with last fiscal year's deficit reaching nearly 1.3 trillion. Meanwhile, many of the euro nations with large amounts of public debt have come close to bankruptcy and loss of capital market access. The same may soon be true of many US states and localities, with the governor of California, for example, publicly regretting that he has been forced to cut bone, and not just fat, from the state's budget. Chartalist economists have long attributed the seemingly limitless borrowing ability of the US government to a particular kind of monetary system, one in which money is a creature of the state and the government can create as much currency and bank reserves as it needs to pay its bills (this is not to say that it lacks the power to impose taxes). In this paper, we examine this situation in light of recent discussions of possible limits to the federal government's use of debt and the Federal Reserve's printing press. We examine and compare the fiscal situations in the United States and the eurozone, and suggest that the US system works well, but that some changes must be made to macro policy if the United States and the world as a whole are to avoid another deep recession.
Keywords: E00; E32; E50; E62; E63; 330; budget deficit; federal debt; debt tolerances